O papel da delegacia da mulher no município de Aracaju no combate à violência doméstica contra a mulher - Almeida, Geilsa Alves (2010)
This survey aims to study the importance of the Women's Police Station in gender conflicts resolution and the effectiveness in meeting to the protection and assistance to the woman who suffers domestic and family violence, whereas its relationship with the existence or not of specific programs directed to this problematic. The present work analyzes the process of implementing such public policies from empirical data collected along the Station Specialized women`s defence; focuses on the process of articulation between the plurality of actors and interests. This review is a qualitative research and part of the construction of a theoretical landmark, analyzes data documentary sources and covers a sample of the various participants. Discusses about domestic violence against women, focusing also on the issues relevant to the elucidation of this thematic, demystify the dichotomy between the public and private sphere and explicit symbolic dimension of domestic violence as a violation of the human rights and fundamental freedoms